Assessment strategies and decision making in male–male contests of Servaea incana jumping spiders. (March 2015) - McGinley, Rowan H.; Prenter, John; Taylor, Phillip W.
Abstract : Animals often engage in contests that have the potential to result in substantial costs in time, energy and risk of injury. To reduce the costs of contests, animals are expected to assess the resource-holding potential of their rivals and compare it to their own as a means of economically determining a winner ('mutual assessment'). If information about the rival is difficult or costly to obtain, rivals may instead reduce the costs of fighting by withdrawing when an individual cost threshold is reached ('self-assessment'). Here we investigated the assessment strategies used by Servaea incana jumping spiders to resolve male–male contests. To examine the effects of body size on contest outcome and strategy, contests were staged between size-unmatched and size-matched pairs. Contests escalated through distinct stages that were of increasing intensity, and body size was a strong predictor of contest outcome. To gain insight into assessment strategy, we considered duration and escalation as measures of cost accrual. Overall, the relations of body size to contest duration and escalation suggest that the decision of whether to retreat during the early noncontact contest phase is largely determined by size-associated internal cost thresholds. Body size was not related to either duration or escalation in the contact phase of contests. We highlight the need to consider appropriateness of proxies used for contest costs and whether game-theoretical predictions for whole contests apply to stages within a contest. Highlights: Contests were staged between size-unmatched and size-matched Servaea incana Larger spiders tended to win contests between size-unmatched pairs. Size of the smaller spider predicted escalation of size-unmatched pairs. Average size predicted escalation of size-matched pairs. Escalation patterns were consistent with own-size dependent persistence.